Starchitects in Bohemia: An Exploration of Cultural Cities from the "Top-Down" and "Bottom-Up". Issue 6 (November 2021) - Jeong, Hyesun; Patterson, Matt
Urban scholars have devoted significant attention to the "cultural city, " but less attention has been paid to how different forms of culture relate to each other and to the larger urban environment. In this article, we compare two quintessential forms of culture-led urbanization that represent opposite ends on a spectrum: iconic architecture and neo-bohemia. While iconic architecture is a "top-down" approach to culture involving large budgets, elite "starchitects, " and powerful clients, neo-bohemia tends to be a "bottom-up" phenomenon formed as individual artists gravitate toward particular neighborhoods, establishing arts scenes. Using a combination of neighborhood case studies and national-level quantitative analysis, we investigate the ecological relationship between these two phenomena. In doing so, we provide new insights into the geographic and social structure of the cultural city.